2016
DOI: 10.15407/ujpe61.07.0597
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Spin-1/2 J1 – J'1 – J2 Heisenberg Model within Jordan–Wigner Transformation

Abstract: The Jordan-Wigner transformation is applied to the spatially anisotropic spin-1/2 Heisenberg model on a square lattice with the nearest-neighbor and next-nearest-neighbor antiferromagnetic interactions. The transformed Hamiltonian describes the interacting spinless fermions that hop between neighbor sites in a gauge field. Using the mean-field-type approximation to both the direct interaction between fermions and the phase factors, which represent the gauge field, the problem is reduced to that concerning a fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 59 publications
(128 reference statements)
0
0
0
Order By: Relevance
“…Among the set of works, where rigorous results were obtained due to the implementation of the onedimensional Jordan-Wigner transformation, there can be mentioned, for example, those, where the Hamiltonian contains not only two-spin interactions but also three-spin ones (see, e.g., works [17][18][19][20][21][22][23][24]). In particular, papers [23,24] were devoted to the study of one-dimensional magnetoelectrics, where the coupling of localized spins (i.e., magnetic moments) with the electric polarization of the bond connecting those spins is described by the Katsura-Nagaosa-Balatsky mechanism [25].…”
Section: Jordan-wigner Transformationmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the set of works, where rigorous results were obtained due to the implementation of the onedimensional Jordan-Wigner transformation, there can be mentioned, for example, those, where the Hamiltonian contains not only two-spin interactions but also three-spin ones (see, e.g., works [17][18][19][20][21][22][23][24]). In particular, papers [23,24] were devoted to the study of one-dimensional magnetoelectrics, where the coupling of localized spins (i.e., magnetic moments) with the electric polarization of the bond connecting those spins is described by the Katsura-Nagaosa-Balatsky mechanism [25].…”
Section: Jordan-wigner Transformationmentioning
confidence: 99%
“…Among the set of works, where rigorous results were obtained due to the implementation of the onedimensional Jordan-Wigner transformation, there can be mentioned, for example, those, where the Hamiltonian contains not only two-spin interactions but also three-spin ones (see, e.g., works [17][18][19][20][21][22][23][24]). In particular, papers [23,24] were devoted to the study of one-dimensional magnetoelectrics, where the coupling of localized spins (i.e., magnetic moments) with the electric polarization of the bond connecting those spins is described by the Katsura-Nagaosa-Balatsky mechanism [25]. Menchyshyn et al [23] showed that the additional account for three-spin interactions can result in a non-trivial magnetoelectric effect (the induction of the electric polarization by a magnetic field at the zero electric field and vice versa), which is not realized in 1D magnetoelectrics with only pair exchanges [26][27][28].…”
Section: Jordan-wigner Transformationmentioning
confidence: 99%
See 2 more Smart Citations